Impact of socioeconomic status and medical conditions on health and healthcare utilization among aging Ghanaians - Saeed, B.I.; Xicang, Z.; YawsonA, A.E.; Nguah, S.B.; Nsowah-Nuamah, N.N.N. (BioMed Central Ltd., 2015)
Background: This study attempts to examine the impact of socioeconomic and medical conditions in health and healthcare utilization among older adults in Ghana. Five separate models with varying input variables were estimated for each response variable. Methods: Data (Wave 1 data) were drawn from the World Health Organization Global Ageing and Adult Health (SAGE) conducted during 2007-2008 and included a total of 4770 respondents aged 50+ and 803 aged 18-49 in Ghana. Ordered logits was estimated for self-rated health, and binary logits for functional limitation and healthcare utilization. Results: Our results show that the study provides enough grounds for further research on the interplay between socioeconomic and medical conditions on one hand and the health of the aged on the other. Controlling for socioeconomic status substantially contributes significantly to utilization. Also, aged women experience worse health than men, as shown by functioning assessment, self-rated health, chronic conditions and functional limitations. Women have higher rates of healthcare utilization, as shown by significantly higher rates of hospitalization and outpatient encounters. Conclusion: Expansion of the national health insurance scheme to cover the entire older population- for those in both formal and informal employments- is likely to garner increased access and improved health states for the older population. © 2015 Saeed et al.; licensee BioMed Central.
Keywords: Aged Ghanaians; Functioning assessment; Healthcare utilization; Socioeconomic status; Subjective health